2018
DOI: 10.1136/bjophthalmol-2017-311051
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the safety and efficacy of intracameral cefuroxime, moxifloxacin and vancomycin at the end of cataract surgery: a meta-analysis

Abstract: Intracameral cefuroxime and moxifloxacin reduced endophthalmitis rates compared with controls with minimal or no toxicity events at standard doses. Additionally, intracameral antibiotics alone may be as effective as intracameral plus topical antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 76 publications
6
79
0
3
Order By: Relevance
“…Another large retrospective study examined more than 57 000 eyes found 8.78‐fold risk reduction attributed to using vancomycin in the irrigation solution, similar to our practice . A meta‐analysis evaluating vancomycin efficacy including 154 669 eyes in which vancomycin bolus dose was most commonly used, found an odds ratio of 0.09 in favour of using intracameral vancomycin . Intracameral vancomycin had the lowest rate of endophthalmitis 0.0106%, compared with moxifloxacin 0.0153% and cefuroxime 0.0332% …”
Section: Microbial Spectrum Of Endophthalmitis Samples Isolated Betwesupporting
confidence: 68%
See 4 more Smart Citations
“…Another large retrospective study examined more than 57 000 eyes found 8.78‐fold risk reduction attributed to using vancomycin in the irrigation solution, similar to our practice . A meta‐analysis evaluating vancomycin efficacy including 154 669 eyes in which vancomycin bolus dose was most commonly used, found an odds ratio of 0.09 in favour of using intracameral vancomycin . Intracameral vancomycin had the lowest rate of endophthalmitis 0.0106%, compared with moxifloxacin 0.0153% and cefuroxime 0.0332% …”
Section: Microbial Spectrum Of Endophthalmitis Samples Isolated Betwesupporting
confidence: 68%
“…Alternative intracameral antibiotics commonly used for endophthalmitis prophylaxis are cefuroxime and moxifloxacin. Cefuroxime is the only antibiotic found to be effective in a randomized controlled study, with further evidence of efficacy in a recently published meta‐analysis . This study also found more complications reported with intracameral cefuroxime compared with vancomycin and moxifloxacin.…”
Section: Microbial Spectrum Of Endophthalmitis Samples Isolated Betwesupporting
confidence: 53%
See 3 more Smart Citations